Acclimating Acculturation of the International Students in the USA - Khan, Md Sharif (Journal of Innovation in Education and Social Research, 2025)
Each year, universities in the United States receive a high number of students from different countries globally. Most of these students underestimate the challenges they could encounter while in the United States. The main goal of this essay is to examine the complex components of acculturation and shine light on important ideas that prospective international students should be fully aware of before they travel. This study will thus examine the methods used by overseas students to deliberately familiarize themselves to the American culture, language, and traditions, thereby enhancing their intellectual prowess and personal development. In order to determine the issues faced by international students at the University level in terms of acculturation, an online survey was conducted in the context of foreign students studying in the US, with a particular emphasis on students within educational institutions where English is the primary language of teaching. The data was collected and analyzed on Minitab for possible correlations between questions that were related to the three hypotheses guiding the study. The first hypothesis proposed that students who can communicate well with native and non-native speakers are likely to learn the language and acculturate faster. This hypothesis was accepted based on the statistical analysis conducted on the data. The second hypothesis argued that students who do good research about the university and are prepared mentally will adapt to the situation more easily than those who do not. This hypothesis was rejected based on the statistical analysis conducted on the data. The final hypothesis proposed that students who are more open toward the host country's culture will eventually adjust better. This hypothesis was accepted. This study concluded that proficiency in the host country language and cultural tolerance lowered the probability of getting acculturative stress. From the study’s findings, it was proposed that Universities should increase opportunities for international students to socially interact with students and citizens of the host country to make them more tolerant to the host country’s culture.